Polyacetal resin, lithography film-forming composition, lithography underlayer film and resist pattern forming method

A polyacetal resin formed by polymerizing a polyhydric phenolic compound and a polyfunctional vinyl ether compound addresses the challenges of solubility, film formability, and heat resistance in lithography materials, enhancing semiconductor manufacturing processes.

JP2025002726APending Publication Date: 2025-01-09KANSAI UNIVERSITY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023103064
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-23
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Conventional lithography materials struggle to simultaneously achieve high solubility in safe solvents, excellent film formability, high heat resistance, and film flexibility, which are essential for advanced semiconductor manufacturing processes.

Method used

A polyacetal resin is developed by addition polymerizing a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound, specifically formulated to enhance solubility, film formability, and heat resistance.

Benefits of technology

The polyacetal resin exhibits high solubility in solvents, excellent film-forming properties, and high heat resistance, enabling the formation of lithography films with improved flexibility and rectangularity, suitable for advanced semiconductor manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002726000031
    Figure 2025002726000031
  • Figure 2025002726000001
    Figure 2025002726000001
  • Figure 2025002726000002
    Figure 2025002726000002
Patent Text Reader

Abstract

To provide a polyacetal resin with high solvent solubility, excellent film-forming properties, high heat resistance, and excellent thickness loss properties, as well as a lithography film-forming composition, a lithography underlayer film, and a resist pattern forming method, containing the polyacetal resin.SOLUTION: The present invention provides a polyacetal resin produced by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound, as well as a lithography film-forming composition containing the polyacetal resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyacetal resin, a lithography film-forming composition, a lithography underlayer film, and a method for forming a resist pattern. [Background technology]

[0002] In the manufacture of semiconductor devices, microfabrication is carried out by lithography using photoresist materials. In recent years, however, with the increasing integration and speed of LSIs (large-scale integrated circuits), there is a demand for further miniaturization using pattern rules. Conventional resist materials are polymeric resist materials capable of forming amorphous thin films. Examples of polymeric resist materials include polymethyl methacrylate, polyhydroxystyrene or polyalkyl methacrylate having an acid-dissociable group. Therefore, photoresist materials that can accommodate finer patterns are being developed. For example, Patent Document 1 discloses a composition containing a resin having a structural unit derived from an ascorbic acid derivative as a composition for a resist film that has high sensitivity and high solubility in a solvent. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2021 / 049472 Summary of the Invention [Problem to be solved by the invention]

[0004] It has been difficult to obtain lithography materials that satisfy all the requirements simultaneously with conventional materials. For example, in the semiconductor manufacturing process, solubility in highly safe solvents is required, while heat resistance is also required. In addition, film-forming properties and suppression of film loss are also required at the same time. Therefore, there is a demand for lithography materials that can satisfy all of these requirements at the same time. Therefore, an object of the present invention is to provide a polyacetal resin which has high solubility in a solvent, excellent film-forming properties, high heat resistance, and excellent film-thinning properties. [Means for solving the problem]

[0005] The present inventors have found that a polyacetal resin obtained by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound can solve the above problems, and have thus completed the present invention.

[0006] That is, the present invention is as follows. <1> A polyacetal resin obtained by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound. <2> The polyhydric phenol compound is at least one selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2), and the polyfunctional vinyl ether group-containing compound is a compound represented by the following formula (3): <1> The polyacetal resin according to claim 1. [ka] (In the formula, X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, and Y is a hydrogen atom or a chlorine atom. R 1 is a hydrogen atom, a methyl group, or an ethyl group. W is an n-valent aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, a heterocyclic group, or a group in which two or more of these are bonded together, and is a group having 1 to 120 carbon atoms. The aliphatic hydrocarbon group, the alicyclic hydrocarbon group, the aromatic hydrocarbon group, the heterocyclic group, and a group in which two or more of these are bonded together may have an alkyl group, a hydroxyl group, an alkoxy group, a carboxyl group, an alkoxycarbonyl group, an acyl group, an amino group, a sulfo group, a halogen atom, a cyano group, or a nitro group as a substituent. n is an integer of 2 to 8. <3> The polyhydric phenol compound is at least one selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2), and the polyfunctional vinyl ether group-containing compound is at least one selected from the group consisting of a compound represented by the following formula (4), a compound represented by the following formula (5), a compound represented by the following formula (6), and a compound represented by the following formula (7), <1> or <2> The polyacetal resin according to claim 1. [ka] (In the formula, X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, and Y is a hydrogen atom or a chlorine atom. R 1 is a hydrogen atom, a methyl group, or an ethyl group; R is a group represented by formula (8), and R 2 is a hydrogen atom, a methyl group, or an ethyl group. <4> A polyacetal resin containing a structural unit represented by the following general formula (9): [ka] (In the formula, X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-; Y is a hydrogen atom or a chlorine atom; Z is at least one group selected from the group consisting of formula (4a), formula (5a), formula (6a), and formula (7a); OA is a group represented by formula (8a); R 2 is a hydrogen atom, a methyl group, or an ethyl group. [ka] <5> The above <1> ~ <4> 13. A film-forming composition comprising the polyacetal resin according to claim 12. <6> The above <1> ~ <4> 10. A lithographic film-forming composition comprising the polyacetal resin according to claim 9. <7> The above further contains a solvent. <6> The lithographic film-forming composition according to claim 1 . <8> The composition contains at least one selected from the group consisting of an acid generator and an acid crosslinking agent. <6> or <7> The lithographic film-forming composition according to claim 1 . <9> The above-mentioned is a lithography underlayer film forming composition. <6> ~ <8> 13. The lithographic film-forming composition according to claim 12, <10> The above <9> A lithographic underlayer film formed from the lithographic film-forming composition according to claim 1. <11> On the substrate, <9> forming an underlayer film precursor using the lithography film-forming composition according to claim 1, and heating the underlayer film precursor to 300° C. or higher to form an underlayer film; forming at least one photoresist layer on the underlayer film; and irradiating the photoresist layer with radiation and developing it; A method for forming a resist pattern comprising the steps of: Effect of the Invention

[0007] According to the present invention, it is possible to provide a polyacetal resin which has high solubility in a solvent, excellent film-forming properties, high heat resistance, and excellent film loss properties. [Brief description of the drawings]

[0008] [Figure 1] 1 shows an example of sensitivity curves (EB sensitivity evaluation) of Examples 9 and 12 (upper part of FIG. 1: Example 9, lower part of FIG. 1: Example 12). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Polyacetal resin] The polyacetal resin of the present invention is a polyacetal resin obtained by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound.

[0010] <Polyphenolic compounds> The polyhydric phenol compound used as a raw material for the polyacetal resin of the present invention is preferably at least one selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2), and more preferably the compound represented by the following formula (1). [ka] (In the formula, X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, and Y is a hydrogen atom or a chlorine atom. R 1 is a hydrogen atom, a methyl group, or an ethyl group.

[0011] In formula (1) and formula (2), Y is a hydrogen atom or a chlorine atom, and is preferably a hydrogen atom. In formula (1), X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, preferably at least one selected from the group consisting of -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, more preferably at least one selected from the group consisting of -S-, -C(CH3)2-, and -C(CF3)2-, and even more preferably -C(CF3)2-. In formula (2), R 1 is a hydrogen atom, a methyl group or an ethyl group, and is preferably a hydrogen atom.

[0012] A specific example of the compound represented by formula (1), from the viewpoints of solubility, film-forming property, heat resistance, film-thinning property and sensitivity, is preferably at least one selected from the group consisting of a compound represented by the following formula (11), a compound represented by the following formula (12), a compound represented by the following formula (13), a compound represented by the following formula (14), a compound represented by the following formula (15), a compound represented by the following formula (16) and a compound represented by the following formula (17), more preferably at least one selected from the group consisting of a compound represented by the following formula (11), a compound represented by the following formula (12), a compound represented by the following formula (13) and a compound represented by the following formula (14), even more preferably at least one selected from the group consisting of a compound represented by the following formula (11), a compound represented by the following formula (12) and a compound represented by the following formula (13), and even more preferably a compound represented by the following formula (13). [ka]

[0013] <Polyfunctional vinyl ether group-containing compound> The polyfunctional vinyl ether group-containing compound used as a raw material for the polyacetal resin of the present invention is preferably a compound represented by the following formula (3). [ka] (In the formula, W represents an n-valent aliphatic hydrocarbon group, alicyclic hydrocarbon group, aromatic hydrocarbon group, heterocyclic group, or group in which two or more of these are bonded together and has 1 to 120 carbon atoms. The aliphatic hydrocarbon group, alicyclic hydrocarbon group, aromatic hydrocarbon group, heterocyclic group, and group in which two or more of these are bonded together may have an alkyl group, a hydroxyl group, an alkoxy group, a carboxyl group, an alkoxycarbonyl group, an acyl group, an amino group, a sulfo group, a halogen atom, a cyano group, or a nitro group as a substituent. n is an integer of 2 to 8.)

[0014] In formula (3), W is an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, a heterocyclic group or a group in which two or more of these are bonded together and has 1 to 120 carbon atoms. Furthermore, the aliphatic hydrocarbon group, alicyclic hydrocarbon group, aromatic hydrocarbon group, heterocyclic group, or a group in which two or more of these are bonded, which constitutes W, may have an alkyl group, a hydroxyl group, an alkoxy group, a carboxyl group, an alkoxycarbonyl group, an acyl group, an amino group, a sulfo group, a halogen atom, a cyano group, or a nitro group as a substituent. N vinyl ether groups are bonded to W. Therefore, W is an n-valent group. In formula (3), n is an integer of 2 to 8, preferably an integer of 2 to 4, more preferably 2 or 3, and further preferably 3. n represents the valence of W.

[0015] More specifically, the polyfunctional vinyl ether group-containing compound is preferably at least one selected from the group consisting of a compound represented by the following formula (4), a compound represented by the following formula (5), a compound represented by the following formula (6), and a compound represented by the following formula (7), more preferably at least one selected from the group consisting of a compound represented by the following formula (4), a compound represented by the following formula (5), and a compound represented by the following formula (6), even more preferably at least one selected from the group consisting of a compound represented by the following formula (4) and a compound represented by the following formula (5), and even more preferably a compound represented by the following formula (5). [ka] (In the formula, R is a group represented by formula (8), and R 2 is a hydrogen atom, a methyl group, or an ethyl group.

[0016] In formula (5), R 2 is a hydrogen atom, a methyl group or an ethyl group, and is preferably a hydrogen atom.

[0017] There is no limitation on the method for synthesizing the polyfunctional vinyl ether group-containing compound, but it is preferable to synthesize the compound from the corresponding polyhydric alcohol and chloroethyl vinyl ether by the Williamson synthesis method.

[0018] <Polyacetal resin structure> The polyacetal resin of the present invention is preferably a polyacetal resin containing a constitutional unit represented by the following general formula (9). [ka] (In formula (9), X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-; Y is a hydrogen atom or a chlorine atom; Z is at least one group selected from the group consisting of formula (4a), formula (5a), formula (6a), and formula (7a); OA is a group represented by formula (8a); R 2 is a hydrogen atom, a methyl group, or an ethyl group. [ka]

[0019] In formula (9), Y is a hydrogen atom or a chlorine atom, and is preferably a hydrogen atom. In formula (9), X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, preferably at least one selected from the group consisting of -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, more preferably at least one selected from the group consisting of -S-, -C(CH3)2-, and -C(CF3)2-, and even more preferably -C(CF3)2-.

[0020] Specific examples of the structural unit represented by formula (9) are, from the viewpoints of solubility, film-forming properties, heat resistance, film loss properties and sensitivity, preferably at least one selected from the group consisting of structural units represented by the following formula (11a), structural units represented by the following formula (12a), structural units represented by the following formula (13a), structural units represented by the following formula (14a), structural units represented by the following formula (15a), structural units represented by the following formula (16a) and structural units represented by the following formula (17a), more preferably at least one selected from the group consisting of structural units represented by the following formula (11a), structural units represented by the following formula (12a), structural units represented by the following formula (13a) and structural units represented by the following formula (14a), even more preferably at least one selected from the group consisting of structural units represented by the following formula (11a), structural units represented by the following formula (12a) and structural units represented by the following formula (13a), and even more preferably at least one selected from the group consisting of structural units represented by the following formula (11a), structural units represented by the following formula (12a) and structural units represented by the following formula (13a), and even more preferably at least one selected from the group consisting of structural units represented by the following formula (13a). In the following formula, Z has the same meaning as in formula (9). [ka]

[0021] In formula (9), Z is at least one group selected from the group consisting of a group represented by formula (4a), a group represented by formula (5a), a group represented by formula (6a), and a group represented by formula (7a), preferably at least one selected from the group consisting of a group represented by formula (4a), a group represented by formula (5a), and a group represented by formula (6a), more preferably at least one selected from the group consisting of a group represented by formula (4a) and a group represented by formula (5a), and even more preferably a group represented by formula (5a). Here, OA is a group represented by formula (8a). The terminal O atom in formula (8a) represents the O atom (oxygen atom) in OA. That is, OA is O-CH2-CH2-O-CH(CH3)-**, and A is -CH2-CH2-O-CH(CH3)-**. Here, ** represents the site of bonding with the unit represented by formula (9a) described later. In formula (5a), R 2is a hydrogen atom, a methyl group or an ethyl group, and is preferably a hydrogen atom. Since Z has 2 to 8 bonds, 1 to 7 units represented by the following formula (9a) can be further bonded to one Z. In addition, the bonds of the oxygen atom of formula (9) and the oxygen atom of formula (9a) can also be further bonded to Z. In this way, by having Z and the unit represented by formula (9a) (the constitutional unit represented by formula (9)) as a repeating unit, a linear or multi-branched polyacetal resin is obtained. The polyacetal resin of the present invention has the above-mentioned structure, and thus has high solubility in a solvent, excellent film-forming properties, high heat resistance, and excellent film loss properties. [ka] (In formula (9a), X is at least one selected from the group consisting of a single bond, -O-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-, and Y is a hydrogen atom or a chlorine atom.)

[0022] <Characteristics of polyacetal resin> The number average molecular weight of the polyacetal resin of the present invention is preferably 1000 to 10000, more preferably 1500 to 8000, even more preferably 1500 to 5000, and still more preferably 2000 to 5000. When the number average molecular weight is within the above range, the resin has high solvent solubility, excellent film-forming properties, and high heat resistance. The molecular weight distribution (Mw / Mn) of the polyacetal resin of the present invention is preferably 1.5 to 10.0, more preferably 1.5 to 8.0, even more preferably 2.0 to 6.0, and even more preferably 2.0 to 5.0. When the molecular weight distribution is within the above range, the polyacetal resin has high solvent solubility, excellent film-forming properties, and high heat resistance.

[0023] <Production method of polyacetal resin> The polyacetal resin of the present invention may be produced by any method without limitation, so long as it is obtained by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound. The method described below is preferred.

[0024] Specifically, it is more preferable to obtain the copolymer by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound in the presence of an acid catalyst such as pyridinium p-toluenesulfonate (PPTS). The amounts of the polyhydric phenolic compound and the polyfunctional vinyl ether group-containing compound used may be adjusted depending on the properties required for the resin, such as molecular weight, but are preferably determined based on the molar ratio of the phenolic hydroxyl groups of the polyhydric phenolic compound to the vinyl groups of the polyfunctional vinyl ether group-containing compound. The molar ratio of the phenolic hydroxyl groups of the polyhydric phenolic compound to the vinyl groups of the polyfunctional vinyl ether group-containing compound [phenolic hydroxyl groups / vinyl groups] is preferably 2 / 8 to 8 / 2, more preferably 3 / 7 to 7 / 3, even more preferably 4 / 6 to 6 / 4, still more preferably 45 / 55 to 55 / 45, and it is even more preferable that the molar ratios are approximately equal.

[0025] The reaction temperature is preferably 0 to 50° C., more preferably 10 to 50° C., and further preferably 20 to 40° C., and may be at room temperature. The reaction time may be appropriately adjusted depending on the reaction temperature, amount of catalyst, reactivity of the raw materials, target molecular weight, etc., and is preferably 1 to 72 hours, more preferably 2 to 48 hours, and further preferably 2 to 24 hours.

[0026] The reaction may be carried out in the presence of a solvent. Preferred solvents are those in which the resulting polyacetal resin dissolves, more preferred are ether solvents, and even more preferred is tetrahydrofuran. When an acid catalyst is used, the reaction is preferably stopped by introducing a basic substance such as triethylamine. The obtained polyacetal resin is preferably purified by a normal post-treatment. Specifically, it is preferable to remove raw materials and by-products by pouring the reaction mixture into an organic solvent in which the polyacetal resin is not soluble and recovering the precipitate. It is also preferable to dissolve the polyacetal resin in an organic solvent in which the polyacetal resin is soluble and wash with water or the like to remove the catalyst and the like. When the polyacetal resin is obtained as a solution in an organic solvent at the end of the polymerization or at the end of the purification treatment, it is preferable to obtain the polyacetal resin as a solid by concentrating and drying. The polyacetal resin obtained in the above manner has high solubility in a solvent, excellent film-forming properties, high heat resistance, and excellent film loss properties.

[0027] [Film-forming composition] The film-forming composition of the present invention is a film-forming composition containing the polyacetal resin. The film-forming composition is a precursor for forming a film. The film-forming composition of the present invention is useful as a precursor for forming films for various industrial products, but since it contains the polyacetal resin, it is particularly suitable for use as a precursor for films for lithography, films for optical parts, etc.

[0028] [Lithography film-forming composition and lithography underlayer film-forming composition] The lithographic film-forming composition of the present invention is a lithographic film-forming composition containing the polyacetal resin. That is, the lithographic film-forming composition of the present invention is a lithographic film-forming composition containing a polyacetal resin obtained by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound. Also, the lithographic film-forming composition of the present invention is a lithographic film-forming composition containing a polyacetal resin containing a constitutional unit represented by the formula (9). The lithography film-forming composition of the present invention is a composition capable of forming a resist top layer film, a resist underlayer film, etc., and is preferably a lithography underlayer film-forming composition. Since the polyacetal resin contained in the lithography film-forming composition of the present invention has high solubility in a solvent, excellent film-forming property, high heat resistance, and excellent film-removal property, the lithography film-forming composition is preferably used as a lithography underlayer film-forming composition. That is, the lithography underlayer film-forming composition of the present invention is a lithography film-forming composition containing the polyacetal resin. The lithography underlayer film-forming composition of the present invention can form a lithography underlayer film such as a resist underlayer film, and has high heat resistance and excellent solvent solubility. Therefore, the rectangularity of the pattern is excellent. In addition, since the film-forming property is excellent, a good resist pattern shape can be imparted. In addition, the lithography underlayer film-forming composition of the present invention can form a lithography underlayer film with high flatness.

[0029] The lithography underlayer film forming composition of the present invention can be suitably used, for example, in a multi-layer resist method in which a resist underlayer film is further provided between an upper layer resist (photoresist, etc.) and a hard mask or an organic underlayer film. In such a multi-layer resist method, for example, a resist underlayer film is formed on an organic underlayer film or hard mask on a substrate by a coating method or the like, and an upper layer resist (for example, photoresist, electron beam resist, EUV resist) is formed on the resist underlayer film. Then, a resist pattern is formed by exposure and development, and the resist underlayer film is dry-etched using the resist pattern to transfer the pattern, and the organic underlayer film is etched to transfer the pattern, and the substrate is processed using the organic underlayer film. That is, the lithography underlayer film (resist underlayer film) formed using the lithography film-forming composition of the present invention is unlikely to cause intermixing with the upper resist layer, has heat resistance, and can obtain a good rectangular pattern. The lithography film-forming composition of the present invention can also be used in an embodiment in which a plurality of resist underlayer films are laminated. In this case, the position (which layer is laminated) of the resist underlayer film formed using the lithography film-forming composition of the present invention is not particularly limited, and it may be directly under the upper resist layer, may be the layer located closest to the substrate, or may be sandwiched between the resist underlayer films.

[0030] In forming a fine pattern, the resist film tends to be thin in order to prevent the pattern from collapsing. The dry etching for transferring the pattern to the film existing in the lower layer by thinning the resist must have a higher etching rate than the film in the upper layer in order to transfer the pattern. Therefore, the substrate can be covered with the resist underlayer film of the present invention through an organic underlayer film, and the resist film (organic resist film) can be further covered on the organic underlayer film. For example, using a resist underlayer film to which a pattern has been transferred, the organic underlayer film underneath can be dry etched with an oxygen-based gas to transfer the pattern to the organic underlayer film, and then the organic underlayer film to which the pattern has been transferred can be used to process the substrate using a halogen-containing gas. In addition, the resist underlayer film made of the lithography film-forming composition of the present invention has high heat resistance, so it can be used under high-temperature baking conditions.Furthermore, since it has a relatively low molecular weight and low viscosity, it is easy to fill even the corners of a substrate having a step (especially a fine space or hole pattern, etc.), and as a result, the planarization property and filling property tend to be relatively advantageously improved.

[0031] The lithographic film-forming composition of the present invention preferably further contains a solvent in addition to the polyacetal resin, and preferably contains at least one selected from the group consisting of an acid generator and an acid crosslinking agent. Further, as other optional components, the composition may contain an acid or base compound, an acid diffusion controller, an organic polymer compound, a surfactant, a colorant, a curing catalyst, etc. From the viewpoint of coatability and quality stability, the content of the polyacetal resin in the lithography film-forming composition is preferably 0.1 to 70 mass%, more preferably 0.5 to 50 mass%, and further preferably 3.0 to 40 mass%.

[0032] <Solvent> From the viewpoint of improving film-forming properties, the lithographic film-forming composition of the present invention preferably further contains a solvent. The solvent is not particularly limited as long as it dissolves the other components such as the polyacetal resin, but the following solvents are preferred. Examples of the solvent include ethylene glycol monoalkyl ether acetates such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol mono-n-propyl ether acetate, and ethylene glycol mono-n-butyl ether acetate; ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether and ethylene glycol monoethyl ether; propylene glycol monoalkyl ether acetates such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate (PGMEA), propylene glycol mono-n-propyl ether acetate, and propylene glycol mono-n-butyl ether acetate; propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether (PGME) and propylene glycol monoethyl ether; lactate esters such as methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, and n-amyl lactate. Aliphatic carboxylic acid esters such as methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, n-amyl acetate, n-hexyl acetate, methyl propionate, and ethyl propionate; methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-ethoxypropionate, methyl 3-methoxy-2-methylpropionate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, and butyl 3-methoxy-3-methylpropionate. Examples of the solvent include butyl 3-methoxy-3-methylbutyrate, methyl acetoacetate, methyl pyruvate, ethyl pyruvate, and other esters; aromatic hydrocarbons such as toluene and xylene; ketones such as methyl ethyl ketone, 2-heptanone, 3-heptanone, 4-heptanone, cyclopentanone (CPN), and cyclohexanone (CHN); amides such as N,N-dimethylformamide, N-methylacetamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and lactones such as γ-lactone. These solvents can be used alone or in combination. The solvent contained in the lithographic film-forming composition of the present invention is preferably a safe solvent, more preferably at least one selected from PGMEA, PGME, CHN, CPN, 2-heptanone, anisole, butyl acetate, ethyl propionate, and ethyl lactate, and even more preferably at least one selected from PGMEA, PGME, and CHN. From the viewpoints of solubility and film formation, the content of the solvent in the lithographic film-forming composition of the present invention is preferably 100 to 10,000 parts by mass, more preferably 200 to 8,000 parts by mass, and even more preferably 200 to 5,000 parts by mass, relative to 100 parts by mass of the total solid components (components excluding the solvent) of the lithographic film-forming composition.

[0033] <Acid generator> The lithographic film-forming composition of the present invention preferably contains at least one selected from the group consisting of an acid generator and an acid crosslinker, and more preferably contains both an acid generator and an acid crosslinker. The acid generator is preferably an acid generator that generates an acid directly or indirectly when irradiated with any radiation selected from visible light, ultraviolet light, excimer laser, electron beam, extreme ultraviolet light (EUV), X-rays, and ion beams. In the lithographic film-forming composition of the present invention, the content of the acid generator is preferably 0.001 to 49 mass %, more preferably 1 to 40 mass %, still more preferably 3 to 30 mass %, and even more preferably 10 to 25 mass %, based on the total mass of the solid components (components excluding the solvent). By having the content of the acid generator within the above range, a pattern profile with high sensitivity and low edge roughness can be obtained. In the lithography film-forming composition of the present invention, the method of generating the acid is not limited as long as the acid is generated in the system. If an excimer laser is used instead of ultraviolet rays such as g-rays and i-rays, finer processing is possible, and if an electron beam, extreme ultraviolet rays, X-rays, or ion beams are used as high-energy rays, further finer processing is possible.

[0034] The acid generator is not particularly limited, and examples thereof include the compounds disclosed in WO 2017 / 033943. The acid generator is preferably an acid generator having an aromatic ring, more preferably an acid generator having a sulfonate ion having an aryl group, and even more preferably at least one selected from the group consisting of diphenyltrimethylphenylsulfonium p-toluenesulfonate, triphenylsulfonium p-toluenesulfonate, triphenylsulfonium trifluoromethanesulfonate, and triphenylsulfonium nonafluoromethanesulfonate. By using the acid generator, line edge roughness can be reduced.

[0035] The lithography film-forming composition of the present invention preferably further contains a diazonaphthoquinone photoactive compound as an acid generator. The diazonaphthoquinone photoactive compound is a diazonaphthoquinone substance including polymeric and non-polymeric diazonaphthoquinone photoactive compounds, and is not particularly limited as long as it is generally used as a photosensitive component in a positive resist composition, and one or more types can be arbitrarily selected and used. Among these, from the viewpoint of low roughness and solubility, a non-polymeric diazonaphthoquinone photoactive compound is preferable, and a low molecular weight compound is more preferable, and the molecular weight is preferably 1500 or less, more preferably 1200 or less, and even more preferably 1000 or less. A preferred specific example of such a non-polymeric diazonaphthoquinone photoactive compound includes the non-polymeric diazonaphthoquinone photoactive compound disclosed in International Publication No. 2016 / 158881. The acid generator can be used alone or in two or more types.

[0036] <Acid crosslinking agent> The lithographic film-forming composition of the present invention preferably contains an acid crosslinker in order to increase the strength of the pattern whether it is used as a negative resist material or a positive resist material. The acid crosslinking agent is a compound capable of intramolecularly or intermolecularly crosslinking a resin in the presence of an acid generated from an acid generator. Such an acid crosslinking agent is not particularly limited, but may be a compound having one or more crosslinking groups capable of crosslinking a resin. Specific examples of the crosslinkable group include, but are not limited to, (i) hydroxyalkyl groups such as hydroxy (alkyl groups having 1 to 6 carbon atoms), alkoxy (alkyl groups having 1 to 6 carbon atoms), and acetoxy (alkyl groups having 1 to 6 carbon atoms), or groups derived therefrom; (ii) carbonyl groups such as formyl and carboxy (alkyl groups having 1 to 6 carbon atoms), or groups derived therefrom; (iii) dimethylaminomethyl groups, diethylaminomethyl groups, dimethylolaminomethyl groups, diethylolaminomethyl groups, and the like. (iv) glycidyl group-containing groups such as glycidyl ether groups, glycidyl ester groups, and glycidylamino groups; (v) groups derived from aromatic groups such as allyloxy (alkyl groups having 1 to 6 carbon atoms) having 1 to 6 carbon atoms, and aralkyloxy (alkyl groups having 1 to 6 carbon atoms) having 1 to 6 carbon atoms, such as benzyloxymethyl groups and benzoyloxymethyl groups; and (vi) polymerizable multiple bond-containing groups such as vinyl groups and isopropenyl groups. As the crosslinkable group, hydroxyalkyl groups and alkoxyalkyl groups are preferred, and an alkoxymethyl group is more preferred.

[0037] Examples of the acid crosslinking agent include, but are not limited to, (i) methylol group-containing compounds such as methylol group-containing melamine compounds, methylol group-containing benzoguanamine compounds, methylol group-containing urea compounds, methylol group-containing glycoluril compounds, and methylol group-containing phenol compounds; (ii) alkoxyalkyl group-containing compounds such as alkoxyalkyl group-containing melamine compounds, alkoxyalkyl group-containing benzoguanamine compounds, alkoxyalkyl group-containing urea compounds, alkoxyalkyl group-containing glycoluril compounds, and alkoxyalkyl group-containing phenol compounds; (iii) carboxymethyl group-containing compounds such as carboxymethyl group-containing melamine compounds, carboxymethyl group-containing benzoguanamine compounds, carboxymethyl group-containing urea compounds, carboxymethyl group-containing glycoluril compounds, and carboxymethyl group-containing phenol compounds; and (iv) epoxy compounds such as bisphenol A-based epoxy compounds, bisphenol F-based epoxy compounds, bisphenol S-based epoxy compounds, novolac resin-based epoxy compounds, resol resin-based epoxy compounds, and poly(hydroxystyrene)-based epoxy compounds. As the acid crosslinking agent, a compound having a phenolic hydroxyl group, and a compound and resin in which the crosslinking group is introduced into the acidic functional group in an alkali-soluble resin to impart crosslinking properties can be used. In this case, the introduction rate of the crosslinking group is not particularly limited, and is preferably 5 to 100 mol%, more preferably 10 to 60 mol%, and even more preferably 15 to 40 mol% based on the total acidic functional groups in the compound having a phenolic hydroxyl group and the alkali-soluble resin. If it is within the above range, the crosslinking reaction occurs sufficiently, and a decrease in the residual film rate, and a swelling phenomenon or meandering of the pattern, etc. can be avoided, which is preferable.

[0038] In the lithography film-forming composition of the present invention, the acid crosslinker is preferably at least one selected from an alkoxyalkylated urea compound or a resin thereof, or an alkoxyalkylated glycoluril compound or a resin thereof (acid crosslinker (1)), a phenol derivative having 1 to 6 benzene rings in the molecule, having two or more hydroxyalkyl groups or alkoxyalkyl groups in the entire molecule, and the hydroxyalkyl group or alkoxyalkyl group being bonded to any of the benzene rings (acid crosslinker (2)), and a compound having at least one α-hydroxyisopropyl group (acid crosslinker (3)). For example, the compounds disclosed in International Publication No. 2017 / 033943 can be mentioned. In the lithographic film-forming composition of the present invention, the content of the acid crosslinker is preferably 0.5 to 49 mass% based on the total mass of the solid components (components excluding the solvent), more preferably 0.5 to 40 mass%, even more preferably 1 to 30 mass%, and even more preferably 2 to 20 mass%. When the content of the acid crosslinker is 0.5 mass% or more, the effect of suppressing the solubility of the resist film in an alkaline developer is improved, and the reduction in the residual film rate and the occurrence of swelling or meandering of the pattern can be suppressed, which is preferable. In addition, when the content is 49 mass% or less, the reduction in the heat resistance of the resist can be suppressed, which is preferable. In addition, the contents of the acid crosslinking agent (1), the acid crosslinking agent (2), and the acid crosslinking agent (3) in the acid crosslinking agent are not particularly limited and can be selected depending on factors such as the type of substrate used when forming a resist pattern.

[0039] [Lithography underlayer] The polyacetal-based resin contained in the lithography film-forming composition of the present invention has high solubility in solvents, excellent film-forming properties, high heat resistance, and excellent film loss properties, so it is preferable to form a lithography underlayer film using the lithography film-forming composition. That is, the lithography underlayer film of the present invention is a lithography underlayer film formed from the lithography film-forming composition. The lithography underlayer film of the present invention can be suitably used as an underlayer (resist underlayer film) of a photoresist (upper layer) used in a multilayer resist method. The lithography underlayer film of the present invention is not particularly limited in its formation method as long as it is formed from the lithography film-forming composition, and known methods can be applied. For example, the lithography underlayer film can be formed by applying the lithography film-forming composition onto a substrate by known coating or printing methods such as spin coating or screen printing, and then removing the organic solvent. Among them, it is preferable to form the lithography underlayer film by the method described in the "step of forming an underlayer film" in the pattern formation method described later.

[0040] [Pattern formation method] As described above, the lithography film-forming composition is excellent as a material for forming a lithography underlayer film, so it is preferable to form a pattern by a pattern forming method having a step of forming a lithography underlayer film on a substrate using the lithography film-forming composition. The pattern formed by such a pattern forming method can be used as a resist pattern. More specifically, a suitable pattern forming method of the present invention is a method for forming a resist pattern, comprising the steps of forming an underlayer film precursor on a substrate using the lithography film-forming composition, and heating the underlayer film precursor to 300° C. or higher to form an underlayer film, forming at least one photoresist layer on the underlayer film, and irradiating the photoresist layer with radiation and performing development.

[0041] <Process for forming underlayer film> The step of forming an underlayer film is a step of forming an underlayer film precursor on a substrate using the lithography film-forming composition, and heating the underlayer film precursor to 300° C. or higher to form an underlayer film.

[0042] The substrate used in this process may be a semiconductor substrate. The semiconductor substrate may generally be a silicon substrate, but is not particularly limited to such a substrate. The substrate may be made of a material different from that of the layer to be processed, such as Si, amorphous silicon (α-Si), p-Si, SiO2, SiN, SiON, W, TiN, or Al. When a semiconductor substrate is used, a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, or a metal oxide nitride film may be formed on the semiconductor substrate as a layer to be processed (a portion to be processed). Examples of the layer to be processed that includes such metal include Si, SiO2, SiN, SiON, SiOC, p-Si, α-Si, TiN, WSi, BPSG, SOG, Cr, CrO, CrON, MoSi, W, W-Si, Al, Cu, Al-Si, and various low dielectric films and their etching stopper films, and can be formed to a thickness of usually 50 to 10,000 nm, particularly 100 to 5,000 nm.

[0043] This step is a step of forming an underlayer film on a substrate using the lithography film-forming composition, but before forming an underlayer film using the lithography film-forming composition, an organic underlayer film or an organic hard mask can be formed on the substrate. Among them, the organic underlayer film can be formed from a coating-type organic underlayer film material using a spin coating method or the like, and the organic hard mask can be formed from an organic hard mask material mainly composed of carbon using a CVD method. The types of such organic underlayer film and organic hard mask are not particularly limited, but when the upper resist film is patterned by exposure, it is preferable that the organic underlayer film and organic hard mask have a sufficient anti-reflective film function. By forming such an organic underlayer film or organic hard mask, the pattern formed by the upper resist film can be transferred onto the substrate (workpiece) without causing a size conversion difference. Note that a hard mask "mainly composed of carbon" means a hard mask in which 50 mass% or more of the solid content is composed of a carbon-based material such as amorphous hydrogenated carbon, also called amorphous carbon and indicated as aC:H. The aC:H film can be deposited by various techniques, but plasma enhanced chemical vapor deposition (PECVD) is widely used due to its cost-effectiveness and film quality controllability. Examples of the hard mask can be found in JP2013-526783A. In the case of forming an organic underlayer film on a substrate, this process is a process of forming an organic underlayer film on a substrate, forming an underlayer film precursor on the organic underlayer film using the lithography film-forming composition, and heating the underlayer film precursor to 300°C or higher to form an underlayer film. In addition, in the case of forming an organic hard mask on a substrate, this process is a process of forming an organic hard mask on a substrate, forming an underlayer film precursor on the organic hard mask using the lithography film-forming composition, and heating the underlayer film precursor to 300°C or higher to form an underlayer film.

[0044] The method for forming the underlayer film precursor using the lithography film-forming composition is preferably to form the composition on a substrate by spin coating or on a workpiece provided with an organic underlayer film, etc. Next, the organic solvent is volatilized and removed to form the underlayer film precursor. Furthermore, when forming the underlayer film, it is preferable to perform a baking treatment in which the underlayer film is heated to 300°C or higher in order to suppress the occurrence of a mixing phenomenon with the upper resist layer and promote a crosslinking reaction. In this case, the baking temperature is preferably 300°C or higher, more preferably 300 to 450°C, and even more preferably 300 to 400°C. The baking time is not particularly limited, but is preferably 10 to 300 seconds. In this manner, the underlayer film is formed on the substrate. The thickness of the underlayer film can be appropriately selected depending on the required performance, and is not particularly limited, but is preferably 30 to 20,000 nm, and more preferably 50 to 15,000 nm.

[0045] <Step of forming photoresist layer> Next, a step of forming a photoresist layer is performed. The step of forming a photoresist layer is a step of forming at least one photoresist layer on the underlayer film.

[0046] This process is a process for forming a photoresist layer on an underlayer film. Examples of photoresist materials used for the photoresist layer include those that form a photoresist film, expose it, and then dissolve the exposed areas using an alkaline developer to form a positive pattern, and those that dissolve the unexposed areas using a developer made of an organic solvent to form a negative pattern. When forming a photoresist layer using a photoresist material, a wet process such as spin coating or screen printing is preferably used. After applying the photoresist material by spin coating or the like, pre-baking is usually performed, and this pre-baking is preferably performed under the conditions of a baking temperature of 80 to 180° C. and a baking time of 10 to 300 seconds. The thickness of the photoresist layer is not particularly limited, but is generally preferably 30 to 500 nm, more preferably 50 to 400 nm.

[0047] <Developing process> Next, a development process is carried out. The developing step is a step of irradiating the photoresist layer with radiation and developing it. In this step, exposure and development are carried out as described above, thereby obtaining a resist pattern.

[0048] The radiation (exposure light) to be irradiated to the photoresist layer may be appropriately selected depending on the photoresist material used. In general, high-energy rays having a wavelength of 300 nm or less, specifically, excimer lasers having wavelengths of 248 nm, 193 nm, and 157 nm, soft X-rays having wavelengths of 3 to 20 nm, electron beams, X-rays, etc., can be used. As a method for forming a pattern, any of the following methods can be suitably used: lithography using light with a wavelength of 300 nm or less or EUV light; electron beam direct writing; and directed self-organization. By using such a method, a fine pattern can be formed. The developing method may be appropriately selected depending on the photoresist material that is the raw material of the photoresist layer used. When a positive pattern is to be formed, it is preferable to form a positive pattern by dissolving the exposed areas using an alkaline developer, and when a negative pattern is to be formed, it is preferable to form a negative pattern by dissolving the unexposed areas using a developer consisting of an organic solvent. In this manner, a resist pattern can be obtained.

[0049] Furthermore, the pattern formation method of the present invention preferably includes the steps of: transferring a pattern to an underlayer film by etching using the resist pattern formed on the upper layer as described above as a mask; transferring a pattern to the organic underlayer film by etching using the resist underlayer film to which the pattern has been transferred as a mask; and further transferring a pattern to the substrate (workpiece) by etching using the organic underlayer film to which the pattern has been transferred as a mask. As another embodiment of the pattern formation method of the present invention, it is preferable that the pattern formation method of the present invention includes the steps of transferring a pattern to the underlayer film by etching using the resist pattern formed on the upper layer as described above as a mask, transferring a pattern to the organic hard mask by etching using the underlayer film to which the pattern has been transferred as a mask, and further transferring a pattern to the substrate (workpiece) by etching using the organic hard mask to which the pattern has been transferred as a mask. EXAMPLES

[0050] The present invention will be described in detail below based on the following examples, but the present invention is not limited to these examples.

[0051] [analysis] Fourier transform infrared spectroscopy (FT-IR) spectra were measured using a JASCO FT / IR4200 (manufactured by JASCO Corporation). 1 The 1 H NMR spectrum was measured using an FTECS-400K (manufactured by JEOL Ltd.) under the conditions of a frequency of 400 MHz, CDCl 3 as a solvent, and Me 4 Si (TMS) as an internal standard. The number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the resin were measured by size exclusion chromatography (SEC) under the following conditions. Standard polystyrene (narrow molecular weight distribution, 0.5 to 1000 kg / mol) was used for calibration. (Measurement conditions: Apparatus: HLC-8220 SEC apparatus, manufactured by Tosoh Corporation; Columns: TSKgel Super AW3000, AW2500 x 2; Detection: RI; Eluent: DMF solution of LiBr and phosphoric acid (20 mM); Flow rate: 0.6 mL / min)

[0052] [Rating 1] <Solubility> The solubility of the resin was confirmed in the following solvents at room temperature (25°C). The solvents tested were NMP (N-methylpyrrolidone), DMSO (dimethyl sulfoxide), DMF (N,N-dimethylformamide), ethyl acetate, acetone, chloroform, PGMEA, and MEK (methyl ethyl ketone). If 2 mg or more of the resin dissolved in 2 g of the above solvents, the solubility was deemed "good."

[0053] <Thermal stability (heat resistance)> The thermal stability was evaluated using a thermogravimetric analyzer (TGA) TGA-50 / 50H (manufactured by Shimadzu Corporation) by heating under nitrogen at a heating rate of 10° C. / min. The higher the initial decomposition temperature (Tdi), the more excellent the thermal stability. Since the polyacetal resin of the present invention has excellent thermal stability as described below, when used as a photoresist material, it can withstand high temperatures of about 100° C. during pre-baking and post-baking (PEB).

[0054] <Film forming and film loss properties> A methyl ethyl ketone (MEK) solution of polyacetal resin (60 mg of resin, 2.0 g of MEK) was applied by spin coating onto a silicon wafer treated with hexamethyldisilane (HMDS) to form a thin film of approximately 100 nm in thickness. The film thickness was measured using a film thickness measuring device (Ellipsometer SE-101 (manufactured by Photonic Lattice Co., Ltd.), surface profiling system Dektak-XT (manufactured by Bruker)) (measurement wavelength: 636 nm). Regarding the film-formability, if the above-mentioned thin film could be formed, the film-formability was rated as "good." Next, the film thickness was measured after immersion in a 2.38 mass % aqueous solution of TMAH (tetramethyl ammonium hydroxide). The difference between the film thickness before and after immersion in the TMAH aqueous solution was determined, and the value (%) obtained by dividing the difference by the film thickness before immersion in the TMAH aqueous solution was evaluated as the thickness loss property. The smaller the value, the more suppressed the film loss, which is preferable. This is an evaluation of the usefulness of a positive resist material that uses an alkaline developer in particular. The value is preferably 40% or less, more preferably 30% or less, and even more preferably 10% or less, and the closer to zero, the better. As described later, the polyacetal resin of the present invention has excellent adhesion and is suppressed from causing film loss.

[0055] [Raw materials] The raw materials used in the examples and evaluations and their abbreviations are as follows. <Polyphenolic compounds> PDP:4,4'-(Propane-2,2-diyl)diphenol TDP: 4,4'-thiodiphenol PFPD:4,4'-(perfluoropropane-2,2-diyl)diphenol(4,4'-(1,1,1,3,3,3-Hexafluoropropane-2,2-diyl)diphenol) BHSO:bis(4-hydroxyphenyl)sulfone DPE:4,4-dihydroxydiphenyl ether DBP: 4,4'-dihydroxybiphenyl TCP: tetrachlorobisphenol A <Polyfunctional vinyl ether group-containing compound> BVEP: 2,2-Bis「4-{2-(vinyloxy)ethoxy}phenyl」propane (synthesized from bisphenol A and chloroethyl vinyl ether by the Williamson synthesis method.) TVPM: A trihydroxyphenylmethane derivative (compound represented by formula (5)) synthesized from trihydroxyphenylmethane and chloroethyl vinyl ether in the same manner as above. BCA[4]-VE: BCA[4] derivative (compound represented by formula (6)) synthesized from BCA[4] (p-tert-butylcalix[4]arene) and chloroethyl vinyl ether in the same manner as above. BCA[8]-VE: BCA[8] derivative (compound represented by formula (7)) synthesized from BCA[8] (p-tert-butylcalix[8]arene) and chloroethyl vinyl ether in the same manner as above. <Other ingredients> PPTS: pyridinium p-toluenesulfonate (Tokyo Chemical Industry Co., Ltd.) THF: tetrahydrofuran (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. (distilled and dried from sodium benzophenone before use)) TMAHaq: Tetramethyl ammonium hydroxide aqueous solution (2.38% by mass aqueous solution) (manufactured by Tama Chemical Industry Co., Ltd.)

[0056] [Production of linear polyacetal resin] Example 1 (Preparation of poly(PDP-co-BVEP)) [ka] A solution of PDP (3.0 mmol, 0.68 g), BVEP (3.0 mmol, 1.11 g), and PPTS (0.3 mmol, 75 mg) as a catalyst in THF (2.4 mL) was stirred at 25 °C for 12 hours. Then, a small amount of NEt3 was added, and the resulting mixture was poured into a large amount of methanol to precipitate the solids. The solids were collected by decantation. The solid obtained was dissolved in chloroform to obtain a solution. Water was added to the solution for washing. The organic phase (chloroform solution) was washed three times in the same manner. The organic phase was dried over anhydrous magnesium sulfate and concentrated using a rotary evaporator. The concentrate obtained was dried under reduced pressure at room temperature for 24 hours to obtain a linear polyacetal resin (poly(PDP-co-BVEP)) as a white solid (yield: 1.38 g). The analytical results are shown below.

[0057] Yield: 77% Mn=2,880, Mw / Mn=2.01 FT-IR (KBr, cm -1 ): 3398 (νO-H), 2929 (νC-H), 1591 (νC=C of vinyl), 1485 (νC=C of aromatic), 1236 (νC-O of ether), 1130 (νC-O of acetal), 754 (νC-S) 1 H NMR (400 MHz, CDCl3, TMS)δ(ppm): 1.45~1.53 (br d, -CH3), 1.57~1.68 (br, -CH3 of acetal), 3.77~4.25 (br m, -CH2-, >CH- and O-CH2-O), 4.88~4.96 (br, -OH), 5.40~5.56 (br q, >CH- of acetal), 6.50~6.59 (br q, CH2of vinyl ether), 6.68~7.47 (br m, aromatic H)

[0058] Example 2 (Production of poly(TDP-co-BVEP)) The reaction of TDP and BVEP was carried out in the same manner as in Example 1 to obtain a linear polyacetal resin (poly(TDP-co-BVEP)). The analytical results are shown below. Yield: 72% Mn=2,630, Mw / Mn=1.99 FT-IR (KBr, cm -1 ): 3398 (νO-H), 2929 (νC-H), 1591 (νC=C of vinyl), 1485 (νC=C of aromatic), 1236 (νC-O of ether), 1130 (νC-O of acetal), 754 (νC-S) 1H NMR (400 MHz, CDCl3, TMS) δ(ppm): 1.45~1.53 (br d, -CH3), 1.57~1.68 (br, -CH3of acetal), 3.77~4.25 (br m, -CH2-, >CH- and O-CH2-O), 4.88~4.96 (br, -OH), 5.40~5.56 (br q, >CH- of acetal), 6.50~6.59 (br q, CH2of vinyl ether), 6.68~7.47 (br m, aromatic H).

[0059] Example 3 (Production of poly(PFPD-co-BVEP)) A linear polyacetal resin (poly(PFPD-co-BVEP)) was obtained by reacting PFPD with BVEP in the same manner as in Example 1. The analytical results are shown below. Yield: 86% Mn=2,050, Mw / Mn=1.80 FT-IR (KBr, cm -1 ): 3400 (νO-H), 2965 (νC-H), 1611 (νC=C of vinyl), 1513 (νC=C of aromatic), 1250 (νC-O of ether), 1171 (νC-O of acetal), 703 (νC-F) 1 H NMR (400 MHz, CDCl3, TMS) δ(ppm): 1.49~1.59 (br d, -CH3), 1.60~1.77 (br d, -CH3of acetal) 3.78~4.24 (br m, -CH2-, >CH- and O-CH2-O), 4.92~4.98 (br, -OH), 5.49~5.70 (br d, >CH- of acetal), 6.52~6.60 (br q, CH2of vinyl ether), 6.73~7.47 (br, aromatic H).

[0060] [Production of hyperbranched polyacetal resin] Example 4 (Preparation of poly(PDP-co-TVPM)) [ka] A hyperbranched polyacetal resin (poly(PDP-co-TVPM)) was obtained (yield 1.50 g) in the same manner as in Example 1, except that PDP (4.0 mmol, 0.91 g), TVPM (2.7 mmol, 1.34 g), and a THF (5.0 mL) solution of PPTS (4.0 mmol, 0.1 g) were used as a catalyst. The analytical results are shown below. Yield: 67% Mn=3,480, Mw / Mn=3.38 FT-IR (KBr, cm -1 ): 3405 (νO-H), 2933 (νC-H), 1608 (νC=C of vinyl), 1508 (νC=C of aromatic), 1240 (νC-O of ether), 1126 (νC-O of acetal) 1 H NMR (400 MHz, CDCl3, TMS) δ(ppm): 1.45~1.53 (s, -CH3of acetal), 1.53~1.68 (m, -CH3), 3.78~4.27 (br m, -CH2-, O-CH2-O), 4.87~4.93 (br, -OH), 5.28~5.39 (m, >CH- of methine), 5.40~5.51 (br, >CH- of acetal), 6.49 ~ 6.57 (br, CH2of vinyl ether), 6.63~7.15 (br, aromatic H).

[0061] Example 5 (Production of poly(TDP-co-TVPM)) The reaction of TDP and TVPM was carried out in the same manner as in Example 4 to obtain a hyperbranched polyacetal resin (poly(TDP-co-TVPM)). The analytical results are shown below. Yield: 75% Mn = 3,750, Mw / Mn = 2.68 FT-IR (KBr, cm-1 ): 3407 (νO-H), 2933 (νC-H), 1606 (νC=C of vinyl), 1509 (νC=C of aromatic), 1235 (νC-O of ether), 1131 (νC-O of acetal), 752 (νC-S) 1 H NMR (400 MHz, CDCl3, TMS) δ(ppm): 1.44~1.56 (s, -CH3of acetal), 3.80~4.29 (br m, -CH2-, O-CH2-O), 4.86~4.94 (br, -OH), 5.31~5.39 (m, >CH- of methine), 5.40~5.51 (br, >CH- of acetal), 6.49~6.54 (br, CH2of vinyl ether), 6.67~7.34 (br, aromatic H).

[0062] Example 6 (Preparation of poly(PFPD-co-TVPM)) The reaction of PFPD and TVPM was carried out in the same manner as in Example 4 to obtain a hyperbranched polyacetal resin (poly(PFPD-co-TVPM)). The analytical results are shown below. Yield: 56% Mn=5,690, Mw / Mn=2.53 FT-IR (KBr, cm -1 ): 3407 (νO-H), 2931 (νC-H), 1610 (νC=C of vinyl), 1508 (νC=C of aromatic), 1252 (νC-O of ether), 1131 (νC-O of acetal), 703 (νC-F) 1H NMR (400 MHz, CDCl3, TMS) δ(ppm): 1.40~1.59 (s, -CH3of acetal), 3.78~4.30 (br m, -CH2-, O-CH2-O), 4.90~5.28 (br, -OH), 5.28~5.38 (m, >CH- of methine), 5.45 ~ 5.54 (br, >CH- of acetal), 6.47~6.57 (br, CH2of vinyl ether), 7.03~7.31 (br, aromatic H).

[0063] [Production of hyperbranched polyacetal resin] Example 7 (Production of poly(PDP-co-BCA[4]-VE)) [ka] A hyperbranched polyacetal resin (poly(PDP-co-BCA[4]-VE)) was obtained (yield 1.83 g) in the same manner as in Example 1, except that PDP (4.0 mmol, 0.87 g), BCA[4]-VE (2.0 mmol, 1.86 g), and a THF (5.0 mL) solution of PPTS (4.0 mmol, 0.1 g) were used as a catalyst. The analytical results are shown below. Yield: 66% Mn=3,780, Mw / Mn=1.32 FT-IR (KBr, cm -1 ): 3417 (νO-H), 2961 (ν CH), 1605 (νC=C of vinyl), 1507 (νC=C of aromatic), 1234 (νC-O of ether), 1122 (νC-O of acetal) 1H NMR (400 MHz, CDCl3, TMS) δ(ppm): 0.69~1.79 (m, -CH3), 3.06~4.53 (br m, -CH2-, >CH- and O-CH2-O), 4.68~4.82 (br, -OH), 5.31~5.56 (br, >CH- of acetal), 6.42~6.56 (br, CH2of vinyl ether), 6.60~7.28 (br, aromatic H).

[0064] Example 8 (Production of poly(TDP-co-BCA[4]-VE)) The reaction of TDP and BCA[4]-VE was carried out in the same manner as in Example 7 to obtain a hyperbranched polyacetal resin (poly(TDP-co-BCA[4]-VE)). The analytical results are shown below. Yield: 77% Mn=3,050, Mw / Mn=1.39 FT-IR (KBr, cm -1 ): 3433 (νO-H), 2958 (νC-H), 1591 (νC=C of vinyl), 1486 (νC=C of aromatic), 1231 (νC-O of ether), 1122 (νC-O of acetal), 634 (νC-S) 1 H NMR (400 MHz, CDCl3, TMS) δ(ppm): 0.72~1.57 (m, -CH3), 2.96~4.56 (br m, -CH2-, >CH- and O-CH2-O), 4.64~4.77 (br, -OH), 5.27~5.60 (br, >CH- of acetal), 6.39~6.59 (br, CH2of vinyl ether), 6.66~7.32 (br, aromatic H).

[0065] Example 9 (Production of poly(PFPD-co-BCA[4]-VE)) The reaction of PFPD with BCA[4]-VE was carried out in the same manner as in Example 7 to obtain a hyperbranched polyacetal resin (poly(PFPD-co-BCA[4]-VE)). The analytical results are shown below. Yield: 44% Mn=4,590, Mw / Mn=1.20 FT-IR (KBr, cm -1 ): 3434 (νO-H), 2954 (νC-H), 1611 (νC=C of vinyl), 1511 (νC=C of aromatic), 1243 (νC-O of ether), 1173 (νC-O of acetal), 704 (νC-F) 1 H NMR (400 MHz, CDCl3, TMS) δ(ppm): 0.66~1.63 (m, -CH3), 3.07~4.55 (br m, -CH2-, >CH- and O-CH2-O), 4.65~4.77 (br, -OH), 5.36~5.75 (br, >CH- of acetal), 6.40~6,59 (br, CH2of vinyl ether), 6.67~7.34 (br, aromatic H).

[0066] [Production of hyperbranched polyacetal resin] Example 10 (Production of poly(PDP-co-BCA[8]-VE)) [ka] A hyperbranched polyacetal resin (poly(PDP-co-BCA[8]-VE)) was obtained in the same manner as in Example 1, except that PDP (4.0 mmol, 0.87 g), BCA[8]-VE (1.0 mmol, 1.86 g), and a THF (5.0 mL) solution of PPTS (4.0 mmol, 0.1 g) were used as a catalyst. The analytical results are shown below. Yield: 64% Mn=8,190, Mw / Mn=3.29 FT-IR (KBr, cm -1): 3410 (νO-H), 2961 (νC-H), 1609 (νC=C of vinyl), 1507 (νC=C of aromatic), 1237 (νC-O of ether), 1115 (νC-O of acetal) 1 H NMR (400 MHz, CDCl3, TMS) δ(ppm): 0.24~1.39 (m, -CH3), 1.40~1.67 (s, -CH3of acetal), 2.76 ~ 4.31 (br m, -CH2-, >CH- and O-CH2-O), 4.32~4.69 (br, -OH), 5.16~5.51 (br, >CH- of acetal), 5.97~6.37 (br, CH2of vinyl ether), 6.38~7.29 (br, aromatic H).

[0067] Example 11 (Production of poly(TDP-co-BCA[8]-VE)) The reaction of TDP and BCA[8]-VE was carried out in the same manner as in Example 10 to obtain a hyperbranched polyacetal resin (poly(TDP-co-BCA[8]-VE)). The analytical results are shown below. Yield: 68% Mn=4,260. Mw / Mn=1.93 FT-IR (KBr, cm -1 ): 3393 (νO-H), 2955 (νC-H), 1594 (νC=C of vinyl), 1482 (νC=C of aromatic), 1233 (νC-O of ether), 1116 (νC-O of acetal), 682 (νC-S) 1H NMR (400 MHz, CDCl3, TMS) δ(ppm): 0.42~1.58 (m, -CH3), 2.97~4.59 (br m, -CH2-, >CH- and O-CH2-O), 4.68~5.05 (br, -OH), 5.05~5.54 (br, >CH- of acetal), 5.90~6.48 (br, CH2of vinyl ether), 6.49~7.37 (br, aromatic H).

[0068] Example 12 (Production of poly(PFPD-co-BCA[8]-VE)) The reaction of PFPD with BCA[8]-VE was carried out in the same manner as in Example 10 to obtain a hyperbranched polyacetal resin (poly(PFPD-co-BCA[8]-VE)). The analytical results are shown below. Yield: 39% Mn=3,420, Mw / Mn=1.47 FT-IR (KBr, cm -1 ): 3412 (νO-H), 2963 (νC-H), 1617 (νC=C of vinyl), 1515 (νC=C of aromatic), 1246 (νC-O of ether), 1131 (νC-O of acetal), 704 (νC-F) 1 H NMR (400 MHz, CDCl3, TMS) δ(ppm): 0.39~1.61 (m, -CH3), 2.92~4.49 (br m, -CH2-, >CH- and O-CH2-O), 4.77~4.98 (br, -OH), 5.01~5.64 (br, >CH- of acetal), 5.99~6.49 (br, CH2of vinyl ether), 6.50~7.40 (br, aromatic H).

[0069] [Table 1]

[0070] From the results in Table 1, it can be seen that all of the polyacetal resins of the examples have high solubility in solvents, excellent film-forming properties, high heat resistance, and excellent film loss properties. Therefore, it can be seen that the polyacetal resin of the present invention is an excellent material for forming a lithography film, and in particular, an excellent material for forming a lithography underlayer film.

[0071] [Production of hyperbranched polyacetal resin using multiple polyhydric phenol compounds] Examples 13 to 18 (Production of Poly(PFPD-co-PDP-co-TVPM)) [ka] A multi-branched polyacetal resin (Poly(PFPD-co-PDP-co-TVPM)) was obtained in the same manner as in Example 4, except that a total of 10.0 mmol of PFPD and PDP were used as the polyhydric phenolic compound, TVPM (6.6 mmol, 3.32 g) was used as the polyfunctional vinyl ether group-containing compound, and a THF (20.0 mL) solution of PPTS (0.92 mmol, 0.2 g) was used as the catalyst, and the reaction time was 3 hours. The ratio [PFPD / PDP] was 100 / 0, 90 / 10, 75 / 25, 50 / 50, 25 / 75, and 0 / 100. Example 13 is Poly(PFPD-co-TVPM), and Example 18 is Poly(PDP-co-TVPM). The analysis results are shown below.

[0072] Example 13 [PFPD / PDP]=100 / 0, yield 74%, Mn=2690, Mw / Mn=1.54, fluorine content 16.8% Example 14 [PFPD / PDP]=90 / 10, yield 73%, Mn=3170, Mw / Mn=1.65, fluorine content 15.4% Example 15 [PFPD / PDP]=75 / 25, yield 92%, Mn=3030, Mw / Mn=2.93, fluorine content 13.2% Example 16 [PFPD / PDP]=50 / 50, yield 77%, Mn=3660, Mw / Mn=5.30, fluorine content 9.2% Example 17 [PFPD / PDP]=25 / 75, yield 66%, Mn=3690, Mw / Mn=6.17, fluorine content 4.8% Example 18 [PFPD / PDP]=0 / 100, yield 77%, Mn=2250, Mw / Mn=2.53, fluorine content 0%

[0073] Examples 19 to 23 (Production of Poly(TDP-co-PFPD-co-TVPM)) [ka] A hyperbranched polyacetal resin (Poly(TDP-co-PFPD-co-TVPM)) was obtained in the same manner as in Example 13, except that a total of 10.0 mmol of TDP and PFPD was used as the polyhydric phenol compound. The ratio [TDP / PFPD] was 100 / 0, 75 / 25, 50 / 50, 25 / 75, and 0 / 100. Example 19 is Poly(TDP-co-TVPM), and Example 23 is Poly(PFPD-co-TVPM). The analytical results are shown below.

[0074] Example 19 [TDP / PFPD]=100 / 0, yield 64%, Mn=3180, Mw / Mn=2.07, refractive index 1.59 Example 20 [TDP / PFPD]=75 / 25, yield 66%, Mn=2310, Mw / Mn=1.64, refractive index 1.58 Example 21 [TDP / PFPD]=50 / 50, yield 56%, Mn=3130, Mw / Mn=1.74, refractive index 1.56 Example 22 [TDP / PFPD]=25 / 75, yield 43%, Mn=2300, Mw / Mn=1.50, refractive index 1.54 Example 23: [TDP / PFPD]=0 / 100, yield 74%, Mn=2690, Mw / Mn=1.54, refractive index 1.52

[0075] Examples 24 to 28 (Production of Poly(BHSO-co-PFPD-co-TVPM)) [ka] A hyperbranched polyacetal resin (Poly(BHSO-co-PFPD-co-TVPM)) was obtained in the same manner as in Example 13, except that a total of 10.0 mmol of BHSO and PFPD was used as the polyhydric phenol compound. The ratio [BHSO / PFPD] was set to 100 / 0, 75 / 25, 50 / 50, 25 / 75, and 0 / 100. Example 24 is Poly(BHSO-co-TVPM), and Example 28 is Poly(PFPD-co-TVPM). The analytical results are shown below.

[0076] Example 24 [BHSO / PFPD]=100 / 0, yield 64%, Mn=2520, Mw / Mn=1.40, refractive index 1.57 Example 25 [BHSO / PFPD]=75 / 25, yield 62%, Mn=2140, Mw / Mn=1.32, refractive index 1.58 Example 26 [BHSO / PFPD]=50 / 50, yield 63%, Mn=2500, Mw / Mn=1.38, refractive index 1.59 Example 27 [BHSO / PFPD]=25 / 75, yield 76%, Mn=2240, Mw / Mn=1.35, refractive index 1.52 Example 28 [BHSO / PFPD]=0 / 100, yield 74%, Mn=2690, Mw / Mn=1.54, refractive index 1.52

[0077] Examples 29 to 31 (Production of Poly(DPE-co-PDP-co-TVPM)) [ka] A hyperbranched polyacetal resin (Poly(DPE-co-PDP-co-TVPM)) was obtained in the same manner as in Example 13, except that a total of 10.0 mmol of DPE and PDP was used as the polyhydric phenol compound. The ratio [DPE / PDP] was 100 / 0, 50 / 50, or 0 / 100. Example 29 is Poly(DPE-co-TVPM), and Example 31 is Poly(PDP-co-TVPM). The analytical results are shown below.

[0078] Example 29 [DPE / PDP]=100 / 0, yield 82%, Mn=3810, Mw / Mn=2.74, refractive index 1.58 Example 30 [DPE / PDP]=50 / 50, yield 88%, Mn=3500, Mw / Mn=4.46, refractive index 1.58 Example 31 [DPE / PDP]=0 / 100, yield 77%, Mn=2250, Mw / Mn=2.53, refractive index 1.57

[0079] Examples 32 to 34 (Production of Poly(DBP-co-PDP-co-TVPM)) [ka] A hyperbranched polyacetal resin (Poly(DBP-co-PDP-co-TVPM)) was obtained in the same manner as in Example 13, except that a total of 10.0 mmol of DBP and PDP was used as the polyhydric phenol compound. The ratio [DBP / PDP] was 100 / 0, 50 / 50, or 0 / 100. Example 32 is Poly(DBP-co-TVPM), and Example 34 is Poly(PDP-co-TVPM). The analytical results are shown below.

[0080] Example 32 [DBP / PDP]=100 / 0, yield 74%, Mn=2970, Mw / Mn=2.47, refractive index 1.59 Example 33 [DBP / PDP]=50 / 50, yield 76%, Mn=3690, Mw / Mn=4.12, refractive index 1.59 Example 34 [DBP / PDP]=0 / 100, yield 77%, Mn=2250, Mw / Mn=2.53, refractive index 1.57

[0081] Examples 35 to 37 (Production of Poly(TCP-co-PDP-co-TVPM)) [ka] A hyperbranched polyacetal resin (Poly(TCP-co-PDP-co-TVPM)) was obtained in the same manner as in Example 13, except that a total of 10.0 mmol of TCP and PDP was used as the polyhydric phenol compound. The ratio [TCP / PDP] was 100 / 0, 50 / 50, or 0 / 100. Example 35 is Poly(TCP-co-TVPM), and Example 37 is Poly(PDP-co-TVPM). The analytical results are shown below.

[0082] Example 35 [TCP / PDP]=100 / 0, yield 36%, Mn=3000, Mw / Mn=1.44, refractive index 1.58 Example 36 [TCP / PDP]=50 / 50, yield 41%, Mn=2740, Mw / Mn=1.73, refractive index 1.57 Example 37 [TCP / PDP]=0 / 100, yield 77%, Mn=2250, Mw / Mn=2.53, refractive index 1.57

[0083] [Table 2]

[0084] From the results in Table 2, it can be seen that the polyacetal resins of the examples all have high solubility in solvents, excellent film-forming properties, high heat resistance, and excellent film loss properties. Therefore, it can be seen that the polyacetal resin of the present invention is an excellent material for forming a lithography film, and in particular, an excellent material for forming a lithography underlayer film.

[0085] [Rating 2] <Positive resist characteristics> A silicon wafer coated with a polyacetal resin obtained in the same manner as in the film-forming property evaluation was used as a test piece, and the test piece was subjected to the following four types of treatment, and the resin thickness was measured. (A) Unexposed, (B) exposed to UV light using a high-pressure mercury lamp, (C) unexposed test piece developed in a 2.38 mass% TMAH aqueous solution, (D) exposed to UV light using a high-pressure mercury lamp and then developed in a 2.38 mass% TMAH aqueous solution. The smaller the difference in thickness between (B) and (C) and (A), and the larger the difference in thickness between (D) and (A), the more excellent the positive resist properties. The results are shown in Table 3.

[0086] [Table 3]

[0087] The results in Table 3 show that the polyacetal resins of the examples are also excellent as positive resist materials.

[0088] [Rating 3] <Resist sensitivity> A methyl ethyl ketone (MEK) solution of a polyacetal resin (60 mg of resin, 2.0 g of MEK) was dissolved with 10% by mass of TPS-109 (manufactured by Midori Chemical Co., Ltd.) as an acid generator and 100 mol % of TOA (tri-n-octylamine) as an acid diffusion controller, relative to the resin, in a volume of 60 mg of resin. The solution was then filtered through a 0.20 μm PTFE syringe filter to obtain a solution for evaluation. The evaluation solution was then applied by spin coating at 2500 rpm for 30 seconds onto a silicon wafer treated with hexamethyldisilane (HMDS) to form a thin film, which was then prebaked at 90° C. for 60 seconds to obtain a film for evaluation.

[0089] (EB sensitivity evaluation) The obtained film for evaluation was exposed to light using an electron beam lithography system (EB lithography) (EB-ENGINE System, manufactured by Hamamatsu Photonics KK) (accelerating voltage: 50 keV, exposed area size: 1 cm×1 cm). The obtained film was irradiated with EUV using an EUV exposure device (EUVES-7000, manufactured by LithoTech Japan Co., Ltd.) and developed by immersing in ion-exchanged water for 30 seconds. Next, the exposed silicon wafer was subjected to a post-exposure bake (PEB) at 90° C. for 30 seconds. The exposed silicon wafer was developed by immersing it in a 2.38% by mass aqueous TMAH solution at room temperature for 30 seconds, rinsing it with deionized water for 10 seconds, and drying it. The film thickness was measured using an ellipsometer (SE-101, manufactured by Photonic Lattice Co., Ltd.) to obtain a sensitivity curve. The lower the exposure dose at which the film thickness becomes zero, the better the resist sensitivity. Table 4 shows E0 (exposure dose at which the film thickness becomes zero (μC / cm 2 )) is shown.

[0090] (EUV sensitivity evaluation) The obtained evaluation film was irradiated with EUV using an EUV exposure device (EUVES-7000, manufactured by LithoTech Japan Co., Ltd.) and developed by immersing in ion-exchanged water for 30 seconds. The film thickness was measured using an ellipsometer (SE-101, manufactured by Photonic Lattice Co., Ltd.) to obtain a sensitivity curve. The lower the exposure dose at which the film thickness becomes zero, the better the resist sensitivity. Table 4 shows E0 (the exposure dose at which the film thickness becomes zero (mJ / cm 2 )) is shown.

[0091] [Table 4]

[0092] From the results in Table 4, it can be seen that the polyacetal resins of the examples also have excellent resist sensitivity. Furthermore, examples of sensitivity curves are shown in Figure 1 (EB sensitivity evaluation of Examples 9 and 12, upper part of Figure 1: Example 9, lower part of Figure 1: Example 12). The polyacetal resins whose sensitivity curves are shown in Figure 1 show excellent sensitivity, with the film thickness decreasing immediately after exposure, the film thickness becoming zero with a small amount of exposure, and the rate of decrease in the film thickness being also rapid.

Claims

1. A polyacetal resin obtained by addition polymerization of a polyhydric phenolic compound and a polyfunctional vinyl ether group-containing compound.

2. 2. The polyacetal resin according to claim 1, wherein the polyhydric phenol compound is at least one selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2), and the polyfunctional vinyl ether group-containing compound is a compound represented by the following formula (3): 【Chemistry 1】 (In the formula, X is a single bond, —O—, —S—, —SO 2 -, -C(CH 3 ) 2 - and -C(CF 3 ) 2 -, and Y is a hydrogen atom or a chlorine atom. 1 is a hydrogen atom, a methyl group, or an ethyl group. W is an n-valent aliphatic hydrocarbon group, alicyclic hydrocarbon group, aromatic hydrocarbon group, heterocyclic group, or a group in which two or more of these are bonded together, and is a group having 1 to 120 carbon atoms. The aliphatic hydrocarbon group, alicyclic hydrocarbon group, aromatic hydrocarbon group, heterocyclic group, and a group in which two or more of these are bonded together may have an alkyl group, a hydroxyl group, an alkoxy group, a carboxyl group, an alkoxycarbonyl group, an acyl group, an amino group, a sulfo group, a halogen atom, a cyano group, or a nitro group as a substituent. n is an integer of 2 to 8.

3. 2. The polyacetal resin according to claim 1, wherein the polyhydric phenol compound is at least one selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2), and the polyfunctional vinyl ether group-containing compound is at least one selected from the group consisting of a compound represented by the following formula (4), a compound represented by the following formula (5), a compound represented by the following formula (6), and a compound represented by the following formula (7). 【Chemistry 2】 (In the formula, X is a single bond, —O—, —S—, —SO 2 -, -C(CH 3 ) 2 - and -C(CF 3 ) 2 -, and Y is a hydrogen atom or a chlorine atom. 1 is a hydrogen atom, a methyl group, or an ethyl group; R is a group represented by formula (8), 2 is a hydrogen atom, a methyl group, or an ethyl group.

4. A polyacetal resin containing a structural unit represented by the following formula (9): 【Chemistry 3】 (In the formula, X is a single bond, —O—, —S—, —SO 2 -, -C(CH 3 ) 2 - and -C(CF 3 ) 2 -, Y is a hydrogen atom or a chlorine atom, Z is at least one group selected from the group consisting of formula (4a), formula (5a), formula (6a) and formula (7a), OA is a group represented by formula (8a), R 2 is a hydrogen atom, a methyl group, or an ethyl group. 【Chemistry 4】

5. A film-forming composition comprising the polyacetal resin according to any one of claims 1 to 4.

6. A lithographic film-forming composition comprising the polyacetal resin according to any one of claims 1 to 4.

7. The lithographic film-forming composition of claim 6 further comprising a solvent.

8. The lithographic film-forming composition according to claim 7 , comprising at least one selected from the group consisting of an acid generator and an acid crosslinker.

9. The lithographic film-forming composition according to claim 8 , which is a lithographic underlayer film-forming composition.

10. A lithographic underlayer film formed from the lithographic film-forming composition of claim 9.

11. A step of forming an underlayer film precursor on a substrate using the lithography film-forming composition according to claim 9, and heating the underlayer film precursor to 300° C. or higher to form an underlayer film; forming at least one photoresist layer on the underlayer film; and irradiating the photoresist layer with radiation and developing it; A method for forming a resist pattern comprising the steps of:

Citation Information

Patent Citations

  • Compound, resin, composition, resist film, pattern forming method, underlayer film, and optical article

    WO2021049472A1